South-Western century 21 accounting - Ross, Kenton E. (South-Western Cengage Learning, 2004)
The fundamental accounting content you've come to trust from South-Western remains. Century 21 Accounting General Journal Approach begins with a single general journal then moves into special journals in Cycle Two. Each chapter is divided into three or four lessons with corresponding assessment activities right at the point of use. End-of-chapter information has been updated to comply with the Texas essential elements. Also, Automated Accounting, located in every chapter, now includes a Peachtree icon to identify some end-of-chapter problems that can be worked with Peachtree software